The Tradition of Using the Manduaro/Mudawaroh Shawl as a Cultural Heritage of the Local Coastal Communities of West Coast Sumatra - Soeandipratama, Soeandi Malik Pratama; Simatupang, Irfan (Professorline, 2025)
Selendang Manduaro or Mudawaroh is a cultural heritage of the coastal communities of the West Coast, holding significant historical, aesthetic, and philosophical value. This traditional shawl is not only used as an accessory in traditional attire but also carries deep symbolic meanings in various ceremonial traditions, particularly in wedding rituals and social identity. However, modernization and lifestyle changes have led to a decline in its usage and preservation.This study aims to explore the tradition of using Selendang Manduaro within local communities through a literature review approach. An analysis of various academic sources was conducted to understand its history, functions, and preservation strategies. The findings indicate that Selendang Manduaro developed as part of cultural acculturation resulting from international trade since the 14th century. However, its existence is currently threatened due to a lack of education, limited regeneration of artisans, and a lack of innovation in design and marketing. To ensure its continuity, several efforts have been undertaken, such as embroidery skills training, entrepreneurship empowerment, and digital-based marketing. This study emphasizes that the revitalization of Selendang Manduaro requires a strategic approach, including design innovation, early cultural education, and support from communities and the government. With these measures, this traditional shawl can continue to be a vital part of the West Coast’s cultural identity and be passed down to future generations